The Formation of Digital Culture in Building The Character of Students - Royanti, Rina; Hakim, Abdul (Islamic Educational Management Programme, 2023)
This study aims to describe the concept of cultivating digital culture as a means of character building in schools. Digital culture represents a transformation brought about by human habits, shifting from traditional practices to more conducive approaches that foster positive changes in the learning process within educational settings. This research employs a qualitative methodology, utilizing descriptive data analysis through interviews conducted via WhatsApp, alongside other supporting data to enrich the findings. The results indicate that digital culture can effectively contribute to the development of students’ character through its integration into the teaching and learning process. Consequently, digital culture introduces transformative aspects in education, such as the use of projectors, online attendance systems, and digital literacy initiatives. These innovations can revitalize the learning experience in schools. Furthermore, the incorporation of digital culture will yield new impacts, serving as promotional media that enhance school effectiveness and improve the overall quality of education in an effective and efficient manner